2021
DOI: 10.1371/journal.pone.0259737
|View full text |Cite
|
Sign up to set email alerts
|

Mitral valve thickening in acute rheumatic fever as a predictor of late valvar dysfunction

Abstract: Background Rheumatic heart disease (RHD) complicating acute rheumatic fever (ARF) remains an important health problem in developing countries. No definitive diagnostic test for ARF exists and the role of Doppler echocardiography (DEC) for long-term prognostic evaluation following ARF is not well established. Objective To investigate the prognostic value of DEC in patients with ARF as a predictor of chronic valve dysfunction. Methods Prospectively enrolled patients with clinical ARF had a DEC performed soon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…Based on these results, it may be reasonable to consider oral penicillin with good compliance as a viable option for secondary prevention in settings with limited resources. It is well established that the mitral valve is the most affected valve in ARF [2,7,31]. In our study, MR with coexisting AR was the most commonly observed abnormality.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Based on these results, it may be reasonable to consider oral penicillin with good compliance as a viable option for secondary prevention in settings with limited resources. It is well established that the mitral valve is the most affected valve in ARF [2,7,31]. In our study, MR with coexisting AR was the most commonly observed abnormality.…”
Section: Discussionsupporting
confidence: 48%
“…Acute rheumatic fever (ARF) is a multisystem inflammatory autoimmune disease that is caused by group A streptococcal (GAS) infection [1][2][3][4]. ARF varies greatly in severity and organ involvement.…”
Section: Introductionmentioning
confidence: 99%